Why may citrate sodium significantly increase the effectiveness of transarterial chemoembolization in hepatocellular carcinoma?. (December 2021) - Icard, Philippe; Simula, Luca; Wu, Zherui; Berzan, Diana; Sogni, Philippe; Dohan, Anthony; Dautry, Raphael; Coquerel, Antoine; Lincet, Hubert; Loi, Mauro; Fuks, David
Abstract: Hepatocellular carcinoma (HCC) represents the third cause of cancer death in men worldwide, and its increasing incidence can be explained by the increasing occurrence of non-alcoholic steatohepatitis (NASH). HCC prognosis is poor, as its 5-year overall survival is approximately 18 % and most cases are diagnosed at an inoperable advanced stage. Moreover, tumor sensitivity to conventional chemotherapeutics (particularly to cisplatin-based regimen), trans-arterial chemoembolization (cTACE), tyrosine kinase inhibitors, anti-angiogenic molecules and immune checkpoint inhibitors is limited. Oncogenic signaling pathways, such as HIF-1α and RAS/PI3K/AKT, may provoke drug resistance by enhancing the aerobic glycolysis ("Warburg effect") in cancer cells. Indeed, this metabolism, which promotes cancer cell development and aggressiveness, also induces extracellular acidity. In turn, this acidity promotes the protonation of drugs, hence abrogating their internalization, since they are most often weakly basic molecules. Consequently, targeting the Warburg effect in these cancer cells (which in turn would reduce the extracellular acidification) could be an effective strategy to increase the delivery of drugs into the tumor. Phosphofructokinase-1 (PFK1) and its activator PFK2 are the main regulators of glycolysis, and they also couple the enhancement of glycolysis to the activation of key signaling cascades and cell cycle progression. Therefore, targeting this "Gordian Knot" in HCC cells would be of crucial importance. Here, we suggest that this could be achieved by citrate administration at high concentration, because citrate is a physiologic inhibitor of PFK1 and PFK2. As shown in various in vitro studies, including HCC cell lines, administration of high concentrations of citrate inhibits PFK1 and PFK2 (and consequently glycolysis), decreases ATP production, counteracts HIF-1α and PI3K/AKT signaling, induces apoptosis, and sensitizes cells to cisplatin treatment. Administration of high concentrations of citrate in animal models (including Ras-driven tumours) has been shown to effectively inhibit cancer growth, reverse cell dedifferentiation, and neutralize intratumor acidity, without apparent toxicity in animal studies. Citrate may also induce a rapid secretion of pro-inflammatory cytokines by macrophages, and it could favour the destruction of cancer stem cells (CSCs) sustaining tumor recurrence. Consequently, this "citrate strategy" could improve the tumor sensitivity to current treatments of HCC by reducing the extracellular acidity, thus enhancing the delivery of chemotherapeutic drugs into the tumor. Therefore, we propose that this strategy should be explored in clinical trials, in particular to enhance cTACE effectiveness.